2021
DOI: 10.1038/s41598-021-95919-2
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning approach identifies 5-ASA and ulcerative colitis as being linked with higher COVID-19 mortality in patients with IBD

Abstract: Inflammatory bowel diseases (IBD), namely Crohn’s disease (CD) and ulcerative colitis (UC) are chronic inflammation within the gastrointestinal tract. IBD patient conditions and treatments, such as with immunosuppressants, may result in a higher risk of viral and bacterial infection and more severe outcomes of infections. The effect of the clinical and demographic factors on the prognosis of COVID-19 among IBD patients is still a significant area of investigation. The lack of available data on a large set of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(38 reference statements)
0
8
0
1
Order By: Relevance
“…Further studies have confirmed that mortality rate from COVID-19 was similar between patients with IBD and those without (RR 0.95, 95% CI 0.71 to 1.26), however, studies that stratified by disease subtype reported that mortality may be higher in patients with UC compared with Crohn’s disease (RR 1.94, 95% CI 1.22 to 3.10) 24 30. Multivariable analyses from SECURE-IBD suggest that this association is likely to be confounded by age, sex, smoking status and comorbidity 34 49 50…”
Section: Impact Of Ibd On Covid-19mentioning
confidence: 97%
“…Further studies have confirmed that mortality rate from COVID-19 was similar between patients with IBD and those without (RR 0.95, 95% CI 0.71 to 1.26), however, studies that stratified by disease subtype reported that mortality may be higher in patients with UC compared with Crohn’s disease (RR 1.94, 95% CI 1.22 to 3.10) 24 30. Multivariable analyses from SECURE-IBD suggest that this association is likely to be confounded by age, sex, smoking status and comorbidity 34 49 50…”
Section: Impact Of Ibd On Covid-19mentioning
confidence: 97%
“…The authors stated that the number of reported cases in the earliest assessments was too low to fully evaluate the association of 5-ASA in COVID-19 evolution. However, further analysis using a machine learning approach showed that 5-ASA was highly associated with COVID-19/IBD mortality [25], but this finding was not confirmed by another similar predictive model [26]. Considering this information, researchers of the SECURE-IBD registry were very cautious and concluded that the association of 5-ASA and COVID-19 was likely due to reporting bias and/or reporting delays [18].…”
Section: Discussionmentioning
confidence: 95%
“…Vereinzelte Studien ließen vermuten, dass die Mortalität bei Patienten mit Colitis ulcerosa höher ist als bei Patienten mit Morbus Crohn sei (RR 1,94, CI 1,22-3,1) [17,30]. Eine multivariate Analyse des SECURE-IBD-Registers legt jedoch nahe, dass die Assoziation vermutlich durch weitere Risikofaktoren bedingt ist [24,31,32].…”
Section: Leitlinieunclassified